Unicentric Castleman disease in the left adrenal region: a case report and literature review - Wang, Zhen; Shi, Yong; Chen, Yun; Xu, Zhongle; Zheng, Li; Zhang, Yanbin; Xi, Junhua (Frontiers in Oncology, 2025)
BackgroundCastleman disease (CD) is a rare lymphoproliferative disorder that can present either as unicentric (UCD) or multicentric (MCD), with distinct clinical and pathologic features. Involvement of the adrenal region is extremely uncommon, often mimicking more common adrenal tumors such as pheochromocytoma. This report describes a patient with a solitary retroperitoneal lesion in the left adrenal region who was ultimately diagnosed with unicentric Castleman disease (hyaline vascular type).Case presentationA 44-year-old female was admitted for surgical management of a left retroperitoneal lesion initially suspected to be an adrenal tumor, based on imaging studies (including CT and PET-CT). Laboratory tests ruled out pheochromocytoma or endocrine hyperfunction. During robotic-assisted laparoscopic surgery, a well-defined 5-cm lesion adjacent to the left adrenal gland was resected along with regional lymph nodes. Pathological examination confirmed Castleman disease of the hyaline vascular subtype with fibrosis and calcification. Postoperative recovery was uneventful, and the patient was discharged with an excellent prognosis.ConclusionsCastleman disease manifesting in the adrenal region is exceedingly rare and may be easily mistaken for an adrenal neoplasm, especially when imaging reveals a hypervascular retroperitoneal lesion with calcification. This case underscores the importance of including Castleman disease in the differential diagnosis of indeterminate adrenal-region tumors with normal endocrine function. Complete surgical excision typically confers an excellent prognosis for unicentric disease.